PENGARUH CORPORATE SOCIAL REPONSIBILITY, PROFITABILITAS, UKURAN PERUSAHAAN DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Periode Tahun 2013-2015) - Azzahra Dita Reminda; Amries Rusli Tanjung; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to find out the effect of corporate social responsibility, profitability, firm size, and capital intensit on the extent of tax aggresiveness. Independent variables used in this study are corporate social responsibility, profitability, firm size, and capital intensity while the dependent variable in this study is tax aggresiveness are measured using Effective Tax Rate (ETR). The population in this study is the banking company on the Indonesian Stock Exchange listed in 2013-2015. The sample was determined by the purposive sampling method and obtain 30 companies. Type of data used was secondary data obtained from www.idx.co.id or corporate websites. Data analysis conducted with multiple regression model with help of software SPSS version 21,0. Of the result of the testing that has been done, that corporate social responsibility, profitability, and firm size has significant value on tax aggresiveness. Meanwhile capital intensity have no significant effect on tax aggresiveness. Based on total adjusted R-square result proved that variables of corporate social responsibility, profitability, firm size, and capital intensity effect on tax aggresiveness results of 43% while the rest of 57% were affected by other variables that were not performed in this study.Keywords: Corporate Social Responsibility, Profitability, Firm Size, Capital Intensity, Tax Aggresiveness